"It was only a mild concussion": Exploring the description of sports concussion in online news articles. (January 2017) - Ahmed, Osman Hassan; Hall, Eric E.
Abstract: Background/aims: Concussion is widely discussed in online sports news articles, but the terms used to report this injury vary. This study aimed to use a systematic search strategy and explore the description of sports concussion in online sports news articles. Methods: A systematic approach was employed to obtain online articles related to sports concussion from four sports associated with concussion (hockey, football, soccer, and rugby). Included articles were evaluated for the descriptors used in relation to concussion and possible consequences associated with concussion. Data was analysed to determine trends between each sport as well between the countries of origin of the articles. Results: From 200 articles retrieved, 153 were included for analysis. The terms "Head injury" (30.1%) and "Brain injury" (20.9%) were most used to describe a concussive injury, and the most frequently mentioned consequence of concussion was "Chronic Traumatic Encephalopathy" (15%). Modifiers which potentially play down the importance of the injury were noted in 9.8% of the articles, with journalists the primary source of these terms. Conclusions: The variability in reporting of concussion by online news articles may limit the transmission of correct concussion information to the public. To improve the consistency of this reporting, the "Media Concussion Checklist" was developed. Highlights: The mainstream media can influence public perception of concussive injuries. Geographical patterns were seen in the concussion descriptor terms used in online news articles. Journalists were the primary source of concussion modifying terms identified in this study. The "Media Concussion Checklist" aims to assist journalists in reporting on concussion stories.